Drug Mass Transfer Mechanism, Thermodynamics, and In Vitro Release Kinetics of Antioxidant-encapsulated Zeolite Microparticles as a Drug Carrier System - Lyubenova Yaneva, Z. (Chemical and Biochemical Engineering Quarterly, 2018)
The aim of the present study was to develop a new vitamin E-zeolite drug carrier system, and investigate the mass transfer mechanism of the antioxidant encapsulation and release on/from the mineral matrix by thermodynamic and kinetics sorption/desorption experiments and mathematical modelling of the experimental data. The surface, morphological and spectral characteristics of the vitamin and the zeolite were determined by Boehm titration, SEM, FTIR and UV/Vis spectrophotometric analyses. Intraparticle diffusion was not the only rate-limiting mechanism, as the mixed-order kinetics model gave the highest regression coefficient ([R.sup.2]) and lowest SSE, MSE, RMSE, and [AIC.sub.C] values. The thermodynamic study confirmed the endothermic nature of the spontaneous encapsulation process and increased degrees of randomness at the solid-liquid interface. The in vitro release results were best modelled by the zero-order and sigmoidal models. The results obtained are essential for the development of innovative vitamin E-carrier systems for application in human and veterinary medicine. Keywords: vitamin E, zeolite, drug encapsulation/release, kinetics, thermodynamics, mathematical modelling